2007
DOI: 10.1002/mnfr.200700176
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of dietary tomatine against dibenzo[a,l]pyrene (DBP)‐induced liver and stomach tumors in rainbow trout

Abstract: The potential anti-carcinogenic effects of tomatine, a mixture of commercial tomato glycoalkaloids alpha-tomatine and dehydrotomatine (10:1), were examined in the rainbow trout chemoprevention model. Prior to the chemoprevention study, a preliminary toxicity study revealed that tomatine in the diet fed daily at doses from 100 to 2000 parts per million (ppm) for 4 weeks was not toxic to trout. For the tumor study, replicate groups of 105 trout were fed diets containing dibenzo[a,l]pyrene (DBP) alone (224 ppm), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 44 publications
4
46
1
Order By: Relevance
“…15,40 (b) As part of the anticarcinogenic study of feeding tomatine to rainbow trout for 9 months, we found that tomatine did not induce changes in mortality, fish weights, liver weights, or tissue morphology. 33 We also observed a lack of toxicity in hamsters orally fed tomatine. 41 (c) The apparent nontoxicity of tomatine in animal models is reinforced by the fact that Peruvians consume without deleterious effects high-tomatine red tomatoes grown in the Andes mountains 8 and that high-tomatine "pickled green" and "green-fried" tomatoes are part of the human diet.…”
Section: ■ Resultsmentioning
confidence: 77%
“…15,40 (b) As part of the anticarcinogenic study of feeding tomatine to rainbow trout for 9 months, we found that tomatine did not induce changes in mortality, fish weights, liver weights, or tissue morphology. 33 We also observed a lack of toxicity in hamsters orally fed tomatine. 41 (c) The apparent nontoxicity of tomatine in animal models is reinforced by the fact that Peruvians consume without deleterious effects high-tomatine red tomatoes grown in the Andes mountains 8 and that high-tomatine "pickled green" and "green-fried" tomatoes are part of the human diet.…”
Section: ■ Resultsmentioning
confidence: 77%
“…Feeding 2000 ppm of tomatine and 224 ppm of the multiorgan carcinogen dibenzo[a,l]pyrene (DBP) to rainbow trout for 9 months resulted in a reduced incidence of liver and stomach tumors by 41.3 and 36.3%, respectively, as compared to the incidence of tumors observed with DBP alone. 85 This seems to be the first report on the inhibition of tumor growth by dietary α-tomatine.…”
Section: Reviewmentioning
confidence: 95%
“…Deamination by phenylalanine ammonia-lyase commits phenylalanine to the phenylpropanoid pathway, and flow through this pathway should be higher in high-phenolic potatoes. There was Although some recent work shows that some glycoalkaloids can have health-promoting effects, potentially including anti-cancer activity (Friedman, McQuistan, Hendricks, Pereira, & Bailey, 2007), total glycoalkaloid concentrations in the United States must be kept below 20 mg/100 g FW to avoid undesirable side-effects. Primitive germplasm and wild-species tended to have the greatest amount of solanine and chaconine in this survey (Supplementary Table 1).…”
Section: Aromatic Amino Acids and Glycoalkaloidsmentioning
confidence: 99%